Bridging Theory: Evaluating the Content of 'Language Improvement for English Teachers' Through Educators’ Eyes - Shalehah, Hasbuna Nikmah; Nuraisyah, Dhea; Annazah, Syafina; Syahid, Abdul (Universitas Negeri Medan, 2025)
The research aimed to assess English teachers' perceptions of the textbook “Language Improvement for English Teachers” by the British Council, focusing on its role in fostering essential language skills for educators. Using a structured questionnaire with a five-point Likert scale, data were collected from 20 active English teachers. The findings showed that teachers generally valued the textbook's engaging topics, clear instructions, and practical design, though some wanted more task variety to address different learner needs. While the textbook effectively integrated key skills, particularly vocabulary and pronunciation, teachers noted a lack of listening activities. The study also received mixed feedback on cultural relevance, indicating a need for better contextual alignment for Indonesian learners. Overall, the textbook was praised as a valuable classroom resource, especially for lesson planning and supporting teachers' pedagogical goals.